Associating Intelligence of Leaders and Employee Creativity - Hussain, Syed Muzaffar; Jeganathan, Lheela; Gianesan, Krishnavani; Aida, Wan Zhalkiatul; Biafri, Vivi Sylviani; Aulia, Qisthina (Journal of Mental Health and Social Rehabilitation, 2023)
This study investigates the association between leaders’ intelligence on followers’ creativity. This was studying exploring by a) relationship between leaders’ EI and followers’ creativity results; b) relationship between intrinsic motivation and EI c) relationship between intrinsic motivation and followers’ creativity. Questionnaire was used to collect data from organizations of service sector. Eighty-one dyads were collected (leaders and employees). Cross sectional data and convenient sampling used in this study. Data analysis techniques were descriptive, correlation and multiple regression analysis. The findings of the study were not gives significant results. There are some other factors which affect followers’ creativity